Pengaruh Tax Avoidance, Kepemilikan Manajerial dan Kualitas Audit terhadap Cost of Debt: Studi Kasus di Perusahaan Farmasi yang Listing di BEI Tahun 2016-2020 - Sri Lestari Yuli Prastyatini; Erlin Indria Safitri (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to prove whether tax avoidance, managerial ownership, audit quality partially affect the cost of debt of pharmaceutical companies on the Indonesia Stock Exchange for the 2016-2020 period. To prove whether tax avoidance, managerial ownership and audit quality simultaneously affect the cost of debt Pharmaceutical Companies on the Indonesia Stock Exchange 2016-2020 Period. The population used in this study are pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020 which have complete and published financial reports. The type of data used in this research is secondary data. Purposive Sampling Sampling Technique,. Collecting data in this study using the method of documentation. The analysis technique used is multiple linear regression with a significance level of 5%. The results in this study indicate that Tax Avoidance has a positive effect on the Cost Of Debt. Managerial Ownership partially has a positive and significant effect on the Cost Of Debt. Audit quality partially has no effect on the Cost Of Debt. Tax Avoidance, Managerial Ownership and Audit Quality have a simultaneous effect on the Cost Of Debt. Keywords: Tax Avoidance, Managerial Ownership, Audit Quality and Cost of Debt